The Shema in John's Gospel - Baron, Lori A. 1959-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
Das Johannesevangelium verwendet das Schma (Dtn 6,4–5), um die Einheit Jesu mit Gott zu verdeutlichen. Lori A. Baron zeigt, dass das Johannesevangelium gegen den Vorwurf, Jesus habe sich mit Gott gleichgestellt, argumentiert, dass Jesus in der göttlichen Einheit steht. Die Einheit der Jünger Jesu mit Gott und untereinander signalisiert, dass sie die verheißene Wiederherstellung Israels repräsentieren.
"The Shema (Deut 6:4-5) is the lens through which Lori A. Baron explores Johannine Christology and the fraught relationship between John's Gospel and Judaism. She begins by examining the use of the Shema in the Hebrew Bible and Second Temple literature, where it is frequently evoked in scenes of covenant renewal; to support adherence to Jewish law; and in prophetic oracles of restoration. The Shema functions similarly in John's Gospel, where Jesus' unity with God is expressed in terms of the 'oneness' of the Shema (e.g., 10:30; 17:21-23): Jesus is within the divine unity. While the Synoptic Gospels cite the Shema explicitly and while Paul uses the Shema christologically, in John, the Shema is an apologetic foil against accusations of bitheism; it is used polemically against Jesus' opponents; and it signals that followers of Jesus represent the promised restoration of Israel."-- Provided by publisher
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Shema; Bible -- Relation to Deuteronomy; Bible -- Relation to the Old Testament; Bible -- Relation to John; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Thomas Carlyle; Protestant Scholarship On Ancient Judaism; (Normen)Kollisionen; Altes Testament; Neues Testament; Anti-judaism; Anti-judaism; Christology; Old Testament; Second Temple Judaism; John within Judaism; Theologie; Hochschulschrift